CRYPTOCURRENCIES’ PUZZLE - Cornelia POP; Ingrid-Emanuela COLONESCU (Studia Universitatis Babeş-Bolyai Negotia, 2021)
The present paper tries to bring a certain degree of clarity to the cryptocurrencies puzzle by discussing the existing definitions and some classifications identified by academic studies. Further, it investigate, based on various academic studies, the uses of cryptocurrencies and their potential role as alternative money. The regulations regarding the cryptocurrencies are also considered since the spreading of the cryptocurrency phenomenon and the risks associated with the use of cryptocurrencies in various capacities raise problems related to (small) investor protection and anti-money laundering.